(untitled) (Our Nature, 2021)
Species composition, phytosociological status and soil characteristics of Siwalik forest occurring around Raja-Rani wetland, Letang municipality, eastern Nepal was studied. A total of 47 tree species belonging to 40 genera and 26 families were reported. Dominant and co-dominant trees were Shorea robusta (IVI=133.4) and Schima wallichii (IVI=70.6), respectively. In the forest total tree density, basal cover area, seedling density, fallen dead density and dead standing density were 378.4 trees ha-1, 163.7 m2 ha-1, 105250 individual ha-1, 4 trees ha-1 and 1.6 trees ha-1, respectively. Irregular girth class distribution and high stump density (136.8 tree ha-1) denote disturbance. Soil physicochemical characteristics were: acidic soil (pH 4.8), moisture (12.5%), water holding capacity (50.05%), bulk density (1.17 g cm-3), porosity (0.55%), humus (8.6%), organic carbon (0.52%), nitrogen (0.1%), phosphorus (33 kg ha-1), and potassium (300 kg ha-1). Regulating human encroachment to ensure natural regeneration of species to maintain the viability of the Letang Raja-Rani wetland site and integrity of the local ecosystem is strongly recommended.